PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBANTUAN MEDIA PEMBELAJARAN ARTICULATE STORYLINE TERHADAP KEMAMPUAN PEMECAHAN MASALAH PESERTA DIDIK KELAS VIII MTsN 1 PADANGSIDIMPUAN - Rangkuti, Muth Mainnah (Jurnal Edukasi dan Penelitian Matematika, 2024)
The primary objective of student learning is to acquire proficiency in mathematical problem-solving skills. However, their mathematical problem solving skills are still inadequate. Problem-Based Learning (PBL) with Articulate Storyline as learning media is suggested to overcome this problem. This study tested whether PBL can improve students' mathematical problem solving ability on SPLDV material compared to conventional learning in class VIII MTsN 1 Padangsidimpuan. This study used Posttest-Only Control Group Design, a pseudo experiment. Data analysis showed that students in class VIII MTsN 1 Padangsidimpuan who were taught with PBL and Articulate Storyline had superior problem solving skills than students who were taught conventionally.